Penerapan Teknik Sablon sebagai Media Pembelajaran untuk Siswa Siswi di SMA - Mesah Nur Sejati; Aji Wicaksono (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
screen printing is a printing technique that is quite developed in society. Learning is all efforts made by educators so that the learning process occurs in students. A study of current conditions will see how the application of screen printing techniques as a learning medium is an important thing to apply to high school students. Students will have an entrepreneurial spirit that is supported by knowledge about design, so they will produce the expected design work products. With the knowledge that is already in place every day applied to students, children's creativity will still be sufficient to develop in the phase of creating something in design. Presentation of material (classical), group discussion and simulation activities, screen printing techniques and experimental methods. The results of observations using applied methods can produce tote bag products for high school students and students. Through the screen printing technique, this method is an output, especially printed results which involve the finished product of a tote bag, a pouch bag. This technique allows images or designs to be printed with high precision and optimal clarity.